Partial hydrogenation of sunflower oil: Use of edible modifiers of the cis/trans-selectivity - Tonetto, Gabriela Marta (2009)
The partial hydrogenation of sunflower oil with minimum trans-isomer formation is studied, using a Pd/γ-alumina catalyst modified with promoters apt for human consumption: ethyl benzoate and magnesium glycinate. It was found that the hydrogenation rate diminishes with the additions of the modifiers. Regarding the cis/trans-selectivity, significant differences were found: ethyl benzoate promoted the formation of trans-isomers, whereas magnesium glycinate diminished it. The results can be interpreted in terms of different effects: change in the electron density of palladium, which affects the relative adsorption strength of the reactant, intermediates and hydrogen, and a block of part of the surface by the modifiers. Theoretical calculations were performed to support this hypothesis.